Innovation In Renewable Energy Systems: Utilization Of Piezoelectric Sensors On Railway Tracks To Harvest Vibration Energy - FIRJATULLAH AKBAR PUTRA BUDIMAN; Bagas Pandya; Anung Kusuma; Hasna Fadhilah; Puspita Dewi; Alfian Yuda Prasetiyo; Muhamad Nurhadi (Journal of Railway Transportation and Technology, 2025)
Green energy development prioritizes sustainable sources like solar, wind, biomass, and geothermal to combat climate change and resource depletion. In this context, piezoelectric technology offers a promising solution for energy harvesting from vibrations and mechanical stresses, such as those generated by vehicles or trains. This technology converts mechanical pressure into electrical energy via polarization changes within piezoelectric materials. This system has proven effective in powering electronic devices and signaling systems at railway level crossings, especially in remote areas lacking grid access. This study employs a descriptive method with a quantitative approach, utilizing experimental data. Data acquired from experiments conducted with the device positioned at a railway level crossing, observing passing trains and various motor vehicles including cars, trucks, and buses, indicated a generated power of 18,185 watts. With the series installation of ten such devices, a total power output of 165.44 Watts per day can be achieved, which is sufficient to meet the energy demands of the signaling system. The harvested energy powers signaling systems, lighting, and other electronic equipment at level crossings. Implementing this technology not only enhances sustainability through renewable energy use but also reduces reliance on external electricity supplies. Consequently, piezoelectric technology significantly improves operational efficiency and railway safety, particularly at level crossings.